2008
DOI: 10.1080/09064700801959908
|View full text |Cite
|
Sign up to set email alerts
|

Lysine restriction during grower phase on growth performance, blood metabolites, carcass traits and pork quality in grower finisher pigs

Abstract: The effects of lysine restriction during grower phase and realimentation during finisher phase on growth performance, nutrient digestibility, blood metabolites, carcass traits and pork quality were studied. Sixty-four pigs (two castrated males and two females per pen) weighing 34.3495.22 kg were assigned to four dietary treatments. During grower (35Á55 kg), pigs were fed isoenergetic lysine-restricted diets. The different lysine content of diets were 0.950 (NRC recommendation), 0.760, 0.665 and 0.570%, corresp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 37 publications
4
24
2
Order By: Relevance
“…However, contrasting results were obtained in some previous research. Decreased dietary lysine concentration caused decreased plasma concentration of total protein, and the plasma total protein concentration increased along with increasing dietary lysine levels (Cahilly et al., ; Kamalakar et al., ; Whisenhunt & Carter, ; Yang et al., ; Zeng et al., ). The age differences between the pigs used in this study and those used previously by other researchers may explain the discrepancy in this regard.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, contrasting results were obtained in some previous research. Decreased dietary lysine concentration caused decreased plasma concentration of total protein, and the plasma total protein concentration increased along with increasing dietary lysine levels (Cahilly et al., ; Kamalakar et al., ; Whisenhunt & Carter, ; Yang et al., ; Zeng et al., ). The age differences between the pigs used in this study and those used previously by other researchers may explain the discrepancy in this regard.…”
Section: Resultsmentioning
confidence: 99%
“…In the experiments with growing and finishing pigs (Fuller, Reeds, Cadenhead, Seve, & Preston, ; Roy, Lapierre, & Bernier, ; Shelton et al., ), crystalline lysine supplementation increased nitrogen retention and protein accretion and improved animal growth performance. It has been shown that dietary lysine affects plasma concentrations of nutrient metabolites including total protein, albumin (Kamalakar et al., ; Yang et al., ), urea nitrogen (UN) (Fernández‐Fígares, Lachica, Nieto, Rivera‐Ferre, & Aguilera, ; Zeng et al., ), glucose (Zhang et al., ), triglycerides, and cholesterol (Bouyeh & Gevorgyan, ; Skiba, ). However, results from these previous studies were rather inconsistent, and in many cases the dietary concentrations of other AAs were adjusted to constant ratios to lysine based on the ideal protein concept (Baker, Hahn, Chung, & Hahn, ; NRC, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, Lys restriction did not have any impact on intake (e.g. Kamalakar et al, 2009;Zhang et al, 2012), whereas other researchers found that dietary Lys restriction resulted in decreased feed intake (RodriguezSanchez et al, 2011) or in increased feed intake (Yang et al, 2008). Such differences could be caused in part by the method used to formulate Lys-restricted feeds, with some approaches based on varying proportions of main feed ingredients resulting in a decrease in CP, whereas others supply feed with synthetic AA and removing one AA to create Cloutier, Pomar, Létourneau Montminy, Bernier and Pomar a restriction without affecting the CP level.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is some evidence that dietary lysine sufficiency may induce compensatory growth in protein-restricted-refed pigs because lysine is the first major limiting essential amino acid in the most pig diets. However, in these studies, lysine was simply used an indicator of protein restriction, which means that sufficiency in multiple amino acids, not just lysine, may have been involved in compensatory growth (Fabian et al 2002, Yang et al 2008b). This study design were not appropriate for elucidating the mechanism of compensatory growth.…”
Section: Introductionmentioning
confidence: 99%